2019
DOI: 10.1016/j.eurpsy.2019.01.014
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacological management of agitated and aggressive behaviour: A systematic review and meta-analysis

Abstract: Introduction:Non-pharmacological interventions preferably precede pharmacological interventions in acute agitation. Reviews of pharmacological interventions remain descriptive or compare only one compound with several other compounds. The goal of this study is to compute a systematic review and meta-analysis of the effect on restoring calmness after a pharmacological intervention, so a more precise recommendation is possible.Method:A search in Pubmed and Embase was done to isolate RCT’s considering pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 75 publications
0
52
0
1
Order By: Relevance
“…This study has reported varied reduction of PANSS-EC score after 2 h of dosages interventions either in single or combination. PANSS-EC scores decreasing caused by lorazepam, haloperidol, haloperidol and promethazine, haloperidol and midazolam, levomepromazine, aripiprazole, olanzapine, risperidone, ziprasidone, loxapine inhalation, and placebo were 7 points, 7-8 points, 15 points, 8-10 points, 15 points within 90 min, 5-6 points for older subjects, 7-8 points with one exception of smaller reduction points, 7-10 points, 7-8 points that one study has reported the decrease up to 14 points, 3-15 points, 9-11 points, and 2-6 points, respectively [8].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations
“…This study has reported varied reduction of PANSS-EC score after 2 h of dosages interventions either in single or combination. PANSS-EC scores decreasing caused by lorazepam, haloperidol, haloperidol and promethazine, haloperidol and midazolam, levomepromazine, aripiprazole, olanzapine, risperidone, ziprasidone, loxapine inhalation, and placebo were 7 points, 7-8 points, 15 points, 8-10 points, 15 points within 90 min, 5-6 points for older subjects, 7-8 points with one exception of smaller reduction points, 7-10 points, 7-8 points that one study has reported the decrease up to 14 points, 3-15 points, 9-11 points, and 2-6 points, respectively [8].…”
Section: Resultsmentioning
confidence: 92%
“…The side effects in cardiovascular condition have been reported to be QT elongation which can increase the risks of arrhythmia, caused by haloperidol for 0-6% of cases and lorazepam for 7% of cases, while in the use of benzodiazepine, no side effects were found [25]. However, hypotension side effects have been reported for 0-17% due to the consumption of haloperidol [8].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…41 For acute agitation, a recent systematic review of 53 papers concluded that rapid tranquilization can be effectively and safely achieved with haloperidol or with atypical neuroleptics. 42…”
Section: Managementmentioning
confidence: 99%